THE INFLUENCE OF WORK SPIRIT, MOTIVATION ON PERFORMANCE AT SEKUPANG PUSKESMAS - Astriani, Fitri; Indrayani, Indrayani; Khaddafi, Muammar; Kenedy, T. Fazrial (RADJA PUBLIKA, 2022)
Abstract Purpose, - The purpose of this study is to provide an explanation of the effect of work spirit and motivation on employee performance at the Sekupang Health Center. Design/Methodology/Approach – The research method used is a quantitative research approach. Data collection is done by distributing questionnaires to 40 respondents from Sekupang Health Center employees. This study uses multiple linear regression analysis, the software used is SPSS 22. Research findings - These results indicate that morale and motivation have a positive and significant effect on employee performance.